2022
DOI: 10.3390/ma15051950
|View full text |Cite
|
Sign up to set email alerts
|

Classifying High Strength Concrete Mix Design Methods Using Decision Trees

Abstract: Concrete mix design methods are used to determine proportions of concrete ingredients needed for certain workability and strength. Each mix design method operates under certain assumptions and suggests slightly different proportions. It is of great importance that site/construction engineers know the method by which the mix was designed. However, it can be difficult to know the designing method based solely on mix proportions. Hence, in this work, a decision trees model was used to classify high strength concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For instance, a decision tree based model can accurately classify different mix design methods to determine the proportions of concrete ingredients for the desired strength. 207 A random forest based model was proposed to predict the compressive stress and resistivity of electrically conductive cementitious materials. 208 Classification of the crack modes in concrete using a support vector machine learning model was carried out to identify the damage state of the structure.…”
Section: Application Of Microbially Induced Calcium Carbonate Precipi...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a decision tree based model can accurately classify different mix design methods to determine the proportions of concrete ingredients for the desired strength. 207 A random forest based model was proposed to predict the compressive stress and resistivity of electrically conductive cementitious materials. 208 Classification of the crack modes in concrete using a support vector machine learning model was carried out to identify the damage state of the structure.…”
Section: Application Of Microbially Induced Calcium Carbonate Precipi...mentioning
confidence: 99%
“…In addition, there are many other recent studies that are not directly applied to self-healing but have shown applicable approaches to explore self-healing questions in bacteria and supplementary cementitious materials. For instance, a decision tree based model can accurately classify different mix design methods to determine the proportions of concrete ingredients for the desired strength . A random forest based model was proposed to predict the compressive stress and resistivity of electrically conductive cementitious materials .…”
Section: Autonomous Healing Cementitious Materialsmentioning
confidence: 99%
“…[63][64][65][66][67][68][69][70]. Estimations of various characteristics of conventional and advanced concretes, such as durability, thermal characteristics, and mechanical characteristics, have been extensively covered in previous studies [71][72][73][74].…”
Section: Categories Of Machine Learningmentioning
confidence: 99%
“…For example, several studies attempted to create models that accurately predict the properties of construction materials by training on data available in the literature [1][2][3][4]. In addition, many properties of fresh and hardened concrete of many different types have been studied and predicted using ML and deep learning models over the past two decades [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Meanwhile, many studies attempted to increase the predictive power of ML models by introducing more complexities or training them with additional experimental data.…”
Section: Introductionmentioning
confidence: 99%